2011
DOI: 10.2478/v10101-011-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, gender and physical activity on plasma lipid profile

Abstract: Effects of age, gender and physical activity on plasma lipid profile Study aim: To assess the effects of gender, age and engagement in physical activities of elderly subjects on their plasma lipid profiles. Material and methods: Four groups of subjects, n = 11 each, participated in the study: young men (YM) and women (YW), aged 25 - 32 years, and sedentary, elderly men (EM) and women (EW), aged 58 - 66 years; additionally, a group of 7 women (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
2
6
0
1
Order By: Relevance
“…Previous reports have overlooked this effect and worked with leukemia populations with wider age-range for these analyses [1][2][3]5]. The agerelated differences in plasma lipid profiles of healthy individuals have been appreciated by the previous workers [43,44]. We also observed the differences in the lipid profiles of individuals from different agegroups.…”
Section: Discussionsupporting
confidence: 60%
“…Previous reports have overlooked this effect and worked with leukemia populations with wider age-range for these analyses [1][2][3]5]. The agerelated differences in plasma lipid profiles of healthy individuals have been appreciated by the previous workers [43,44]. We also observed the differences in the lipid profiles of individuals from different agegroups.…”
Section: Discussionsupporting
confidence: 60%
“…On the contrary, we have observed a significant positive correlation of TSH and a negative correlation between FT4 levels and the IMCT in hypothyroid group before LT4 treatment ( Figure 4 ). Significant correlation between TSH level and lipid profile was not found probably due to some other parameters, that is, age and diet effects on lipid levels [ 32 , 33 ]. Another possibility could be because of small sample size and small effect size.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis showed differences with HDL (high density lipoprotein) levels between the groups at the beginning of the study, which could be affected by several individual factors of the study population (age, diet, stress, tobacco, alcohol, physical activity, etc.) [33,45,46], which must be considered in future supplementation studies. At the end of study, the concentrations of HDL showed a tendency to increase in experimental group (51.9 to 60.1 mg/dL) and LDL (low density lipoprotein) decreased (69.9 to 62.7 mg/dL) causing the reduction of atherogenic index (2.6 to 2), while the control group showed a contrary behavior.…”
Section: Biochemical Parametersmentioning
confidence: 99%